Effect of reaction parameters on the production of cyclodextrin using cyclodextrin glucanotransferase from bacillus licheniformis - Rohaida, Che Man; Shalyda, Md Shaarani; Zatul Iffah, Mohd Arshad; Siti Kholijah, Abdul Mudalip; Siti Zubaidah, Sulaiman; Aizi Nor Mazila, Ramli (Universiti Malaysia Pahang, 2020)
Cyclodextrin glucanotransferase (CGTase) is an industrial enzyme that converts starch into cyclodextrin (CD). CD has many potential applications in wide range of industries including food, cosmetic, pharmaceutical and plastic industries. Production of CD from CGTase is based on a few process parameters such as concentration of substrate, types of substrate, reaction time, pH and temperature. In this present study, the effect of types of substrate (corn, potato, wheat, rice and tapioca starch), concentration of substrate (1, 2, 3, 4, 5, 6, 7, 8 and 9%) and reaction time (1, 2, 3, 4 and 5 hr) on the CD production using commercial CGTase from Bacillus licheniformis were studied. Among the five types of substrate tested, the potato starch was the most suitable substrate for the production of CD with 10.24 mg/ml of CD. In addition, by using 6% (w/v) of potato starch, the production of CD was 15.16 mg/ml. The optimal reaction time was found to be 4 hr with 12.41 mg/ml of CD. Therefore, the best reaction parameters proved to be valuable for the highest CD production. Hence, CGTase from Bacillus licheniformis was demonstrated to produce high CD at optimum reaction conditions and it has potential to be used in large scale production for the industrial purposes.